40 YEARS EXPERIENCE OF INTERLOCKING INTRAMEDULLARY METALLIC-POLYMERIC OSTEOSYNTHESIS IN TREATMENT OF 1200 PATIENTS WITH SHAFT FRACTURES - Vasiuk V. Le.; Kovalchuk P. Ye.; Zinchenko A. T.; Tulyulyuk S. V. (World Science, 2019)
The article comprises the main principles of interlocking intramedullary metallic-polymeric nailing (IIMPN) and the experience of its implementation in 1200 cases of shaft fractures during the period of 40 years. Three generations of metallic-polymeric nails and techniques for closed, semi-closed and open IIMPN were designed. The nails can successfully be interlocked with proximal and distal bone fragments without an intraoperative X-ray control. Therefore, the operation can be made in any hospital capable of surgical treatment of fractures. Unlike interlocking metallic nailing, the dynamic variant of IIMPN makes the additional operation of dynamization unnecessary. CMPN-3 and CMPN-2 nails have options of intraoperative axial and lateromedial compression between fragments, which is impossible in interlocking metallic nailing. The carving conjunction between screws and polymer, which flexibility is close to that of the bone, excludes critical concentration of tensions and considerable dynamic loadings, and therefore prevents fractures of the interlocking screws. Good follow-up results were obtained in 94.2% patients.